2018
DOI: 10.21680/1517-7874.2018v20n1id13331
|View full text |Cite
|
Sign up to set email alerts
|

Replicando o efeito Takete-Maluma em Português Brasileiro

Abstract: Este artigo tem como objetivo discutir o papel da iconicidade como fenômeno linguístico e trazer evidências empíricas sobre a necessidade dessa discussão. Para tanto, investigamos se falantes de Português Brasileiro (PB) constroem as mesmas relações entre fonemas e categorias perceptuais que falantes de outras línguas, um fenômeno descrito como simbolismo sonoro (STYLES e GAWNE, 2017). Isso foi feito por meio da replicação do experimento Takete-Maluma (KÖHLER, 1929) e uma variação desse teste que tem como obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Regarding the linguistic and cultural background of the participants, it is worth noting that testing languages other than English is beneficial for the field of cross-modal correspondences. We are aware of only one other study on the boubakiki effect in speakers of Portuguese (Godoy et al, 2018).…”
Section: Participantsmentioning
confidence: 99%
“…Regarding the linguistic and cultural background of the participants, it is worth noting that testing languages other than English is beneficial for the field of cross-modal correspondences. We are aware of only one other study on the boubakiki effect in speakers of Portuguese (Godoy et al, 2018).…”
Section: Participantsmentioning
confidence: 99%
“…findings that have been replicated across different languages (Berlin 2006;Newman 1933;Shinohara & Kawahara 2016;Ramachandran & Hubbard 2001;Hollard & Wertheimer 1964;Maurer et al 2006;Nielsen & Rendall 2013 among others), including BP (Godoy et al 2017;Silva and Bellini-Leite 2019). However, a natural question that arises is whether more abstract concepts, like justice and freedom, can be signaled by way of sound symbolism (Lupyan & Winter 2018).…”
Section: Sound Symbolism In Pokémon Namesmentioning
confidence: 99%
“…Apart from corpus-based research on ideophones in regional dialects of BP (Cruz & Fernandes 2004), and acoustic and perceptual analysis of speech expressivity (Madureira & Camargo 2010), few experimental studies have tested the perception or production of sound symbolism. Similar to many languages, behavioral and physiological experiments have shown that speakers of BP are sensitive to sound/shape symbolism while reading or listening to linguistic stimuli (Godoy et al 2017;Silva & Bellini-Leite 2019). In general, sonorants like /m, l/ are associated with round shapes, while voiceless plosives such as /t, k/ are associated with angular and jagged images.…”
Section: Sound Symbolism In Brazilian Portuguesementioning
confidence: 99%